HIV and other sexually transmitted infections among female sex workers in Moscow (Russia): prevalence and associated risk factors. Issue 8 (18th March 2020) - Bernier, Adeline; Rumyantseva, Tatiana; Reques, Laura; Volkova, Natalia; Kyburz, Yan; Maximov, Olga; Derrienic, Eve; Guschin, Alexander; Bouscaillou, Julie; Luhmann, Niklas; Pataut, Dominique
Abstract : To estimate the prevalence and factors associated with HIV and five other STIs among outdoor female sex workers (OSFW) and indoor FSW (IFSW). Methods: Cross-sectional survey using respondent-driven sampling methodology. Participants answered a bio-behavioural questionnaire and were tested for Neisseria gonorrhoeae (NG), Chlamydia trachomatis (CT), Trichomonas vaginalis (TV), syphilis (lifetime contact) and Mycoplasma genitalium (MG). Weighted HIV and other STIs prevalence and 95% CIs were calculated. Weighted multivariate logistic regression was performed to identify factors associated with having at least one STI (including HIV). Results: Between October 2017 and July 2018, 385 FSW participants were recruited, among whom 206 (53.5%) were IFSW and 179 (46.5%) were OFSW. The mean age was 31.4 years. Weighted HIV prevalence was 3.1% (95% CI 1.5 to 7.0). Weighted prevalence of other STIs was: 4.1% (95% CI 2.2 to 8.0) for NG, 8.8% (95% CI 5.9 to 13.0) for CT, 12.7% (95% CI 8.6 to 18.0) for TV, 13.9% (95% CI 9.9 to 19.0) for syphilis (lifetime contact) and 14.9% (95% CI 10.5 to 21.0) for MG. STI prevalence was significantly higher among OFSW for CT, TV and MG (p<0.001). In total, 43.2% of the participants had at least one HIV/STI. Factors associated with having HIV/STI were being an OFSW (OR 3.29; 95% CI 1.72 to 6.27); being registered in another Russian region (2.61 (95% CI 1.05 to 6.48)); having never been tested for HIV (2.51 (95% CI 0.98 to 6.41)) and having a low level of knowledge regarding HIV transmission (4.88 (95% CI 0.96 to 24.78)). Conclusion: Prevalence of HIV and STIs was high among FSW in Moscow. OFSW were more vulnerable to STIs. There is an urgent need to tailor programmes for sexual and reproductive health for FSW in Russia.